An investigation of the mathematics applications in the Apple App Store: Do they contain benchmarks of educational quality? - Alam, Sabrina Shajeen; Wen, Run; Kaçmaz Ekici, Gülşah; Eyyi, Rima; Dube, Adam Kenneth; Ekici, Gülşah Kaçmaz (Routledge Journals, Taylor & Francis Ltd, 2025)
Given the numerous mathematics applications marketed in the Apple App Store and the lack of quality control, it is critical to determine whether these digital learning tools are well-designed and if they are accurately marketed by developers. The present study evaluated the top math apps (n = 33) priced under $15, categorized into three age groups (i.e. <5, 6-8, and 9-11) in the App Store. It examined how well they incorporate five educational features or benchmarks in their apps, namely- scaffolding, feedback, learning theory, math subjects, and content integration (i.e. the connection between game and learning content). Furthermore, it assessed whether developers mentioned these benchmarks in their store descriptions and if the descriptions accurately reflected the app's content. Most apps included more than three benchmarks. All apps contained feedback and learning theory and most provided some forms of scaffolding. The types and amount of math subjects, feedback, and scaffolding varied significantly across apps. Interestingly, these top apps contained more benchmarks and content than developers advertise in the App Store. The findings emphasize the importance of developers incorporating benchmarks into their apps and accurately communicating this to the public to help them navigate the sea of available apps.
Keywords: Math Apps; Educational Benchmarks (Ed-Benchmarks); In-App; Apple App Store